Unraveling the harmful effect of oxidative stress on male fertility: A mechanistic insight - Hussain, Tarique; Kandeel, Mahmoud; Metwally, Elsayed; Murtaza, Ghulam; Kalhoro, Dildar Hussain; Yin, Yulong; Tan, Bie; Chughtai, Muhammad Ismail; Yaseen, Anjaleena; Afzal, Ali; Kalhoro, Muhammad Saleem (Frontiers in Endocrinology, 2023)
Male infertility is a widely debated issue that affects males globally. There are several mechanisms to be involved. Oxidative stress is mainly accepted as a main contributing factor affecting sperm quality and quantity by the overproduction of free radicals. The overwhelming of reactive oxygen species (ROS) could not be controlled by an antioxidant system which thus potentially impacts male infertility and hampers sperm quality parameters. Mitochondria are the driving force of sperm motility; irregularities in its function may lead to apoptosis, alteration in signaling pathway function and ultimately comprised fertility. Moreover, it has been observed that the prevalence of inflammation may arrest sperm function and the production of cytokines triggered by the overproduction of ROS. Further, oxidative stress interacts with seminal plasma proteomes which influence male fertility. Enhanced ROS production disturbs cellular constituents particularly DNA and then sperms unable to impregnate ovum. In this review paper, we will update the information to understand the relationship of oxidative stress with male infertility, mitochondria role, cellular response, inflammation and fertility, interaction of seminal plasma proteomes with oxidative stress and also highlight the influence of oxidative stress on hormones, collectively, all these are assumed to be the important factor for regulation of male infertility. This article may assist in better understanding male infertility and its preventive strategies.